أحكام النفقة الزوجية دراسة مقارنة في الفقه الإسلامي والقانون الجزائري والأردني - • عيسي خيرة; • سعيد نادية (جامعة محمد بوضياف – المسيلة, 2025)
تتناول هذه المذكرة موضوع النفقة الزوجية من زاويتين, الأولى فقهية والثانية قانونية, حيث تعتبر النفقة الزوجية من أهم حقوق الزوجة ولا غنى عنها لتحقيق استقرار الأسرة, وقد سلط الضوء على مفهوم النفقة الزوجية شاملا تعريفها وشروطها ومسقطاتها مع المشتملات في الفقه الإسلامي بمذاهبه الأربعة, مقارنة مع ما نص عليه كل من القانونين الجزائري و الأردني, بالإضافة إلى الآثار القانونية للامتناع عن الانفاق, وقد انطلقت الدراسة من إشكالية تتجسد في مدى توفيق المشرع الجزائري في الإلمام بجميع قضايا النفقة الزوجية في قانون الأسرة, وهدفت هذه الدراسة إلى بيان مفهوم النفقة الزوجية الفقهي والقانوني, ومقارنة أحكام الفقه الإسلامي مع القانونيين الجزائري والأردني. This graduation thesis addresses the topic of marital support from two perspectives: the first one is being jurisprudential and the second is legal. Marital support is regarded as one of the fundamental rights of the wife and it is indispensable for achieving family stability. This thesis highlights the concept of marital support, including its definition, conditions, exemptions, and inclusions in Islamic jurisprudence across its four schools, compared to the stipulations of both the Algerian and Jordanian laws, In addition to the legal ramifications associated with the failure to provide financial support. The study starts with a problem statement reflecting on the extent to which the Algerian legislator has comprehensively addressed all matters related to marital support in family law. The aim of this study is to clarify the concept of marital support from both theological and legal perspectives, alongside a comrision of the legal rulings derived from Islamic juriprudence with those of the Algerian and Jordanian laws.